A Survey of Inconsistency-Adaptive Logics - Batens, Diderik (Frontiers of Paraconsistent Logic, 2000)
This paper offers a systematic review of some central philosophical and technical results on adaptive logics. Quite a few of the results are still in print or forthcoming.